Utilisation of information and communication technologies in distance learning programmes in Southwest, Nigeria (2012)
Distance Learning programmes would simply become impossible tasks without information and communication technologies (ICTs) as well as internet based instructional strategies. These programmes are characterized by learner- centredness, life-long learning, independent learning and recognition of prior learning. Although, the University of Ibadan Distance Learning Centre (UIDLC) is well known for the use of ICTs, more advanced technologies are not prevalent feature of the programmes. This study therefore assessed the level of utilisation of ICTs and internet facilities in the University of Ibadan Distance Learning programmes with respect to their availability and adequacy. The Input- Process- Output evaluation model was employed to guide the study. A sample of 200 participants, selected through multistage sampling procedure was involved in the study. Three research questions guided the study. One validated instrument was used to collect data and its reliability index was 0.86. Data was analyzed using frequency counts and percentages. In terms of availability, usability and adequacy of Information and Communication Technologies: Radio programme service 147(73.5%); Overhead projector 105(52.5%); Video tapes 147(73.5%); Audio tapes 119(59.5%);Computers 145(72.5%); Internet facilities 175(87.5%) and Electronic board 118(59%) were available and in use in the programme, while Interactive television programme service 13(6.5%); Fibre optics 59(29.5%) and Electricity supply were in short supply in the programme. The distance learning institution (UIDLC) is striving to make use of ICTs and Internet facilities on its programmes. However, impact of ICTs goes wider than just the structure and presentation of courses, it must also aim at improving teaching-learning resources, staff capacity development, learner support services, and increase the number of courses available to prospective candidates in order to position distance education in Nigeria for global competitiveness.